Effect of the thrombin receptor antagonist (PAR‐1) vorapaxar on QT/QTc interval in healthy volunteers: A randomized, placebo‐ and positive‐controlled, parallel group trial. Issue 1 (25th September 2013) - Kosoglou, Teddy; Hunt, Thomas L.; Xuan, Fengjuan; Kumar, Bharath; Statkevich, Paul; Hanson, Mary E.; Cutler, David L.
Abstract In a randomized, double‐blind (vorapaxar and placebo), placebo‐ and positive‐controlled (moxifloxacin 400 mg) parallel group study, the effect of single‐dose vorapaxar 120 mg on QT/QTc interval was assessed in 120 adults 18–50 years. Twelve‐lead digital ECGs were obtained in triplicate using Mortara H12+ Holter monitors at 9 timepoints over 24 hours. If the largest upper bound of the 95% one‐sided CI for the mean difference in QTcF between vorapaxar and placebo was <10 milliseconds, vorapaxar was considered to have no potential for QT/QTc prolongation of regulatory concern. Vorapaxar was well‐tolerated. The lower bound of the 95% CI for the difference in QTcF between moxifloxacin and placebo was >5 milliseconds, confirming study sensitivity. Vorapaxar had no significant effect on QTcF. At all timepoints the upper 95% CI for the mean difference between placebo and vorapaxar was ≤3.8 milliseconds (mean difference ≤1.0 milliseconds). Vorapaxar does not prolong the QT/QTc interval in healthy subjects.